2017
DOI: 10.1017/s0144686x16001525
|View full text |Cite
|
Sign up to set email alerts
|

Life in a continuous traumatic situation: perspective of the older population

Abstract: The literature is divided with regard to how older persons cope with traumatic situations of war and terror, and few studies have focused on continuous exposure to traumatic situations. To fill the gap in existing knowledge, the present study examined how older people cope with a continuous security threat which includes periods of intensive attacks. Three focus groups were conducted among older residents of rural localities situated near the Israeli border with Gaza. Content analysis of transcripts from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Many older persons lack family support or become separated from their relatives and friends, 24,25,30,32,34–36,45,55,64 sometimes without the means to contact those who have moved away 64 . Family connectedness fosters security, maintains normalcy and builds resilience during crises, 49 such that the loss of family support networks contributes to social isolation 25,32,35,48 and can have deleterious effects upon the mental health of older persons 25–28,30,34,36,46,48,49,52,53,67 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many older persons lack family support or become separated from their relatives and friends, 24,25,30,32,34–36,45,55,64 sometimes without the means to contact those who have moved away 64 . Family connectedness fosters security, maintains normalcy and builds resilience during crises, 49 such that the loss of family support networks contributes to social isolation 25,32,35,48 and can have deleterious effects upon the mental health of older persons 25–28,30,34,36,46,48,49,52,53,67 …”
Section: Resultsmentioning
confidence: 99%
“…Overarching theme: Conflict situations exacerbate existing inequalities experienced by older persons All included documents contributed to an overarching theme that conflict situations exacerbate existing inequalities related to older persons. These include health and mental health issues [22][23][24][25][26][27][28][29] and associated physical and cognitive limitations, ageism, 22,[30][31][32][33] ableism, financial exclusion (e.g., lack of pension benefits), 24,32,34,35 and social isolation. 25,30,36 Inequalities are most pronounced for older persons living with the intersectional identity of older age, non-Caucasian, female gender, disabled, living in rural and remote communities.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is surprising in light of previous insights that life on the Israel/Gaza border should be seen as life in the shadow of a continuous threat with long-term consequences (Nuttman-Shwartz, 2023), a situation which has a greater likelihood of being experienced as more severe than being exposed to one traumatic event (e.g., Kira et al, 2023). This difference in findings may derive from the fact that the pandemic was perceived as an unknown and unfamiliar phenomenon in contrast to the security threat, which older adults living in this area viewed as a familiar stressor (Nuttman-Shwartz & Regev, 2018). The results of a Stein et al (2018) study indicated that residents living on the Israel/Gaza border had become habituated to the continuous security threats and to cumulative trauma—that is, prior greater exposure has been associated with more resilience during high-intensity attacks.…”
Section: Discussionmentioning
confidence: 99%